DEBRIS FLOW PHENOMENA IN THE ARMENIAN HIGHLAND (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
Spreading of debris flow phenomena in the Armenian Highland in the whole and in particular the RA; natural conditions contributing to the formation of debris flows; their varieties; parameters of the largest debris flows in the territory of Armenia are discussed in the article. Special attention is drawn to the danger of forming of anthropogenic genesis debris flows in view of accumulating a large volume of building and garbage wastes in the river-beds and on the slopes of debris flow streams. Cleaning and deepening of river-beds of debris flow streams and creation of protective barriers using steel nets is proposed as preventive measures for localities protection.
Keywords: Armenian highland; debris flow; preventive measures